Loss of Life and Labor Productivity: The Canadian Opioid Crisis. Issue 1 (September 2022) - Cheung, Alexander; Marchand, Joseph; Mark, Patricia
Opioids were declared a public health emergency in British Columbia, Canada, in 2016, and from that year through 2021, 29, 894 Canadians lost their lives to opioid overdoses. More than two-thirds of those victims were employed in the five years prior to their deaths, and this study aims to quantify their lost productivity to the Canadian economy. We apply two human capital model variants in our analysis, projecting forward the future economic output of individuals who died from opioids, from their deaths to what would have been their eventual retirements, based on the industries in which they were employed. The total estimated productivity loss to Canada is at least 8.8 billion, with the equivalent "value of statistical life" calculations an order of magnitude higher; these are based on estimates of the amount of money that individuals would pay to avoid death. Our results challenge the notion that the opioid crisis predominantly affects unproductive members of society.